Iron-nitrogen dual-doped three-dimensional mesoporous carbons for high-activity electrocatalytic oxygen reduction. (December 2018) - Lin, Gaoxin; Ma, Ruguang; Zhou, Yao; Liu, Qian; Hu, Chun; Yang, Minghui; Wang, Jiacheng
Graphical abstract: Highlights: Mesoporous carbons prepared by hard template using biomass carbon sources. Successful doping of iron and nitrogen into the framework of mesoporous carbons. Uniform pore diameters and large surface areas for the doped mesoporous carbons. Superior oxygen reduction activity with a four-electron pathway for Fe, N-codoped mesoporous carbon. Abstract: To improve the efficiency of oxygen reduction reaction (ORR) on non-precious metal electrocatalyst, designing three-dimensional porous catalysts with abundant exposed active sites, accessible catalytic surface and excellent stability are of significant interest. Herein, we prepared Fe/N co-doped mesoporous carbons (FeNMCs) via a facile aggregation of renewable biomass flour, dicyanamide, colloidal silica and anhydrous ferric chloride, followed by carbonizing at 900 °C in N2 atmosphere. The optimal catalyst (FeNMC-2) possesses interconnected uniform mesopores of ∼12.9 nm, large surface area of 769.5 m 2  g −1, high nitrogen-doping level and atomically dispersed Fe-N x active species. The developed porous texture is advantageous for not only promoting the formation of Fe-N coordinated functional species and the accessibility of catalytic sites, but also facilitating the transport of reactants and products during the ORR process. For the ORR, the optimized FeNMC-2 displays excellent electrocatalytic performance, which even outperforms commercial Pt/C. Furthermore, the control experiments verify that the high ORR activity should be ascribed to uniformly dispersed Fe-N x sites within the framework of 3D porous carbons. The present strategy can be extended to design and prepare other metal, N-co-doped porous carbons with great potentials in energy conversion and storage.